Gentrification influences mosquito community composition at neighborhood and county levels in Miami-Dade County, Florida - Nicole A. Scavo; Chalmers Vasquez; Laura C. Multini; John-Paul Mutebi; André B. B. Wilke (PLoS ONE, 2025)
Gentrification is occurring across urban areas in the United States and poses threats to marginalized and vulnerable communities through displacement, disruption of social networks, and worsening health outcomes. Gentrification is both a social and environmental process, affecting socioecological factors responsible for driving mosquito abundance and community composition. Our study aims to investigate how gentrification in Miami-Dade County, Florida, affects the alpha and beta diversity of mosquito communities. We relied on data from the Miami-Dade County Mosquito Control Division from 2020 to 2024, paired with data from the American Community Survey, to analyze changes in mosquito community composition based on gentrification status. Our results show that gentrification, measured by changes in home value, age, race, and education, significantly affected mosquito richness and community composition at county and neighborhood levels. Culex quinquefasciatus and Aedes aegypti, primary arbovirus vector species, were more abundant in gentrifying areas, representing 31% of community composition variation compared to non-gentrifying areas. These findings have important implications for improving mosquito-borne disease preparedness and response in urban settings.